Monte Carlo simulation results for anaemia detection in the skin - Kallepalli, Akhil; James, David (Cranfield University, 2020)
This research was presented at SPIE Photonics West 2020 (February 2020) with the article titled: Quantification and influence of skin chromophores for remote detection of anemic conditions (https://doi.org/10.1117/12.2545784) Monte Carlo simulations were performed using Virtual Tissue Simulator (VTS) and Monte Carlo Command Line (MCCL) tools. The target was a two-layer model of the epidermis and dermis layers of the skin. The optical attenuation properties quantifying the absorption and scattering in these layers are set according to two parameters: - Amount of melanin in the epidermis - Amount of haemoglobin in the blood-perfused dermis The optical models are simulated at six wavelengths for 6 skin types (Fitzpatrick's scale) and two blood conditions, healthy and anaemic. This results in a total of 72 simulations The simulation calculates the optical interaction of 10 6 photons with the various combinations of optical properties. The resulting outputs show the absorption and fluence in the tissue model, and reflected and transmitted energy.
Keywords: 'Monte Carlo computer simulations'; 'Skin anatomy'; 'anaemia'; 'chromophores'; 'absorption properties'; 'Scattering Properties'; 'photon transport'; 'haemoglobin concentration'; 'Hematocrit (HCT)'; 'erythrocyte concentration'; 'Simulation and Modelling'; 'Applied Physics'; 'Human Biophysics'; 'Biological Physics'; 'Medical Physics'